Kolaborasi Antar Aktor Dalam Pencegahan dan Penanganan Pelecehan Seksual di Universitas Kristen Satya Wacana: (Collaboration Between Actors in Preventing and Handling Sexual Harassment at Satya Wacana Christian University) - Cintana Amara Sadmoko; Sri Suwartiningsih; Rizki Amalia Yanuartha (Sam Ratulangi University, 2024)
Sexual harassment occurs because of the practice of patriarchal domination. The places that still often dominated by cases of sexual harassment are universities. When the facts case of the sexual harassment were discovered, a policy was issued, that was Regulation of the Minister of Education, Culture, Research and Technology Number 30 of 2021 concerning the Prevention and Handling of Sexual Violence in Higher Education Environments. This policy requires all universities, one of which is UKSW, to form a special task force, namely PPKS. PPKS collaborates with several supporting partners to facilitate the flow of task implementation. Apart from officially authorized actors, there are other media in the form of Instagram accounts which indirectly contribute to the prevention and handling of sexual harassment cases. PPKS and other media that are not officially connected have their respective roles and actions in carrying out their duties. So, this research will be analyzed using Bruno Latour's Actor Network Theory with descriptive qualitative methodology which sees reality as